Characterization of clouds in Titan's tropical atmosphere - Griffith, Caitlin A.; Penteado, Paulo; Rodriguez, Sebastien; Le Mouélic, Stephane; Baines, Kevin H.; Buratti, Bonnie J.; Clark, Roger; Nicholson, Phil D.; Jaumann, Ralf; Sotin, Christophe (The Astrophysical Journal, 2009)
Images of Titan's clouds, possible over the past 10 years, indicate primarily discrete convective methane clouds near the south and north poles and an immense stratiform cloud, likely composed of ethane, around the north pole. Here we present spectral images from Cassini's Visual Mapping Infrared Spectrometer that reveal the increasing presence of clouds in Titan's tropical atmosphere. Radiative transfer analyses indicate similarities between summer polar and tropical methane clouds. Like their southern counterparts, tropical clouds consist of particles exceeding 5 μm. They display discrete structures suggestive of convective cumuli. They prevail at a specific latitude band between 8°-20° S, indicative of a circulation origin and the beginning of a circulation turnover. Yet, unlike the high latitude clouds that often reach 45 km altitude, these discrete tropical clouds, so far, remain capped to altitudes below 26 km. Such low convective clouds are consistent with the highly stable atmospheric conditions measured at the Huygens landing site. Their characteristics suggest that Titan's tropical atmosphere has a dry climate unlike the south polar atmosphere, and despite the numerous washes that carve the tropical landscape.